أثر العوامل الإجتماعية على إتخاذ القرار الشرائي: دراسة حالة المستهلك السوداني - الجزولي، فاطمة سراج الدين (جامعة البحر الأحمر, 2015)
The study addressed the impact of social factors on purchasing decision-making for the Sudanese consumers. The study followed the descriptive and analytical approaches were followed. The primary and secondary data were analyzed with the SPSS programme. The most important result of the study were as follows; There is an influence of social factors on the purchasing decision of the Sudanese consumer, The impact of the family was the first influential factor while the impact of famous peoples [Stars of community] was the last influential factor, There are no impact of social factors upon purchasing decision-making of the Sudanese consumer attributable to demographic factor [age, gender, marital status, income and educational level]. The study reached a number of recommendations as follows: The need to focus policies and marketing programs on the needs of the family and to provide products that meet those needs, The provision of suitable places for family shopping, to provide different marketing programs for consumers of all ages and other programs specialize in geneder when formulating the marketing policies.
هدفت الدراسة إلى اكتشاف العلاقة بين العوامل الاجتماعية والخصائص الديمغرافية المؤثرة على القرار الشرائي للمستهلك السوداني. اتبع المنهج الوصفي التحليلي وحللت مصادر البيانات الأولية والثانوية ببرنامج الحزم الإحصائية للعلوم الاجتماعية. توصلت الدراسة إلى مجموعة من النتائج أهمها: وجود تأثير للعوامل الاجتماعية على القرار الشرائي للمستهلك السوداني ويأتي تأثير الأسرة في المرتبة الأولى بالنسبة للعوامل الاجتماعية وتليها الطبقة الاجتماعية (القدرة المالية) ثم تأثير الثقافات بينما احتل كل من الأصدقاء والزملاء والمشاهير (نجوم المجتمع) المراتب الأخيرة على التوالي، عدم وجود تأثير للعوامل الاجتماعية عند اتخاذ القرار الشرائي للمستهلك السوداني يعود للعوامل الديمغرافية (العمر، النوع، الحالة الاجتماعية، الدخل، المستوى التعليمي). من أهم التوصيات ضرورة التركيز في السياسات والبرامج التسويقية على حاجات الأسرة، توفير منتجات تلبي تلك الاحتياجات، توفير أماكن مناسبة للتسوق العائلي، تقديم برامج تسويقية مختلفة للمستهلكين مختلفي الأعمار وأخرى متخصصة في النوع عند صياغة السياسات التسويقية.
Keywords: السياسة الإقتصادية -- العوامل الإجتماعية -- الإستهلاك -- السودان -- المجتمع السوداني -- السياسة التسويقية -- القدرات الشرائية